Hubungan Tingkat Pemahaman dengan Praktik Personal Hygiene pada Lansia di Rumah Pelayanan Sosial Semarang - Septiana Dwi Riskayanti; Iskim Luthfa; Moch. Aspihan (Pusat Riset dan Inovasi Nasional, 2026)
Personal hygiene is an essential factor in maintaining the health and quality of life of the elderly, as aging is often accompanied by a decline in physical strength, mobility, and cognitive function that can reduce the ability to maintain personal cleanliness independently. Limited understanding of the importance of personal hygiene may increase the risk of infections, skin disorders, and other health complications, making education and awareness crucial for promoting better hygiene behavior. This study used a descriptive correlational design with a cross-sectional approach involving 204 elderly individuals residing at the Pucang Gading Elderly Social Service Home in Semarang and Wening Wardoyo Ungaran, with 135 respondents selected using a non-probability sampling technique. Data were collected using validated and reliable questionnaires measuring the level of understanding and personal hygiene practices and were analyzed using the Somers’d statistical test. The results showed that most respondents were female (60%) and aged between 70–79 years (48.9%). The level of understanding of personal hygiene among the elderly was predominantly in the moderate category (72.6%), and their personal hygiene practices were also mostly categorized as moderate (72.6%). Statistical analysis revealed a p-value of 0.000 (<0.05) with a correlation coefficient (r) of 0.472, indicating a positive and significant relationship between the level of understanding and personal hygiene practices. These findings suggest that improving knowledge through continuous education and guidance from health workers is necessary to enhance awareness, independence, and hygiene behavior among the elderly.